The Girl Who Drank the Moon - Barnhill, Kelly Regan (Chapel Hill, North Carolina : Algonquin Young Readers, 2016)
"An epic fantasy about a young girl raised by a witch, a Swamp Monster, and a Perfectly Tiny Dragon, who must unlock the powerful magic buried deep inside her"--
Keywords: Witches -- Juvenile fiction; Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Friendship in children -- Juvenile fiction; Witches -- Fiction; Dragons -- Fiction; Magic -- Fiction; Friendship -- Fiction; Fantasy